(untitled) (Italian Review of Legal History, 2021)
The documents conserved in the Terracini Jewish Archive of Turin allow the reader to examine the application of the legislation concerning Jewish communities during the period of time starting from the Napoleonic domination until the Italian unity. My research focuses in particular on the notarial deeds and judicial documents relating to the property of the synagogue and the cemetery of the Jewish community of Mondovì. Under the rule of France the Jewish people living in Piedmont were allowed to become real estate owners and the plots of land where the Jewish cemetery was located and the house that hosted the synagogue in Mondovì were allotted to the Jewish community. During the Restoration, the ban to become real estate property was introduced again. Even if the Jewish people of Mondovì had bought from its owner the house of the synagogue and they had obtained from the French administration the property of the plots of land of the cemetery, they were not anymore recognized as owners. After the emancipation of the Jewish population and the Italian unity, the Jewish community of Mondovì claimed its rights on those real estate properties: my essay would focus on the exam of the archive documents that show how the legislation concerning real estate property for Jewish people was applied over time.